Pelatihan Keterampilan Teknologi Digital Bagi Warga Belajar di PKBM Banda Khalifah - Saifullah; Ismail (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
Digital technology skills training for learning residents at PKBM Banda Khalifah Peureulak is a program to provide knowledge and skills about using digital technology to people who are not familiar with technology. In the early stages, in general, the participants' ability to operate digital technology still had some obstacles, such as not knowing how to open and close the program properly. In addition, the ability to use computer/laptop devices for office purposes and marketing a product online is still not mastered. This training method consists of several stages, namely: 1) Explanation of Basic Concepts At this stage, participants are explained the basic concepts of digital technology, such as hardware and software, operating systems, applications, and the internet. 2) Practical Use of Hardware After understanding the basic concepts, participants will be taught how to operate hardware devices, such as computers, laptops, smartphones, and printers. 3) Practical Use of Software After mastering the use of hardware, participants will be taught how to operate software, such as Microsoft Office applications, internet browsers, and social media. This program can help participants improve their skills and productivity in various aspects of life, such as work, education, product marketing and communication. In addition, this program is also to increase digital inclusivity and strengthen people's access to digital technology. In its implementation, this program involves instructors who are competent and skilled in the field of digital technology.